P657 Current landscape of the real-world utilization of Interleukins 22, 23 and Interleukin 22 binding protein as biomarkers for Inflammatory Bowel Disease (IBD): A targeted literature review. (30th January 2023) - Dolin, P; Evans, K; Castañeda, J; Udayachalerm, S; Cabrera, C
Abstract: Background: Precision medicine is an active area of IBD research. Evidence underpinning the role of IL-22, IL-23, and IL-22 binding protein (BP) as biomarkers of mechanistic pathways, diagnosis, disease severity, and treatment response has been accumulating. Little is known about the applications of these ILs as biomarkers in real-world studies. The aim of this literature review was to describe the current landscape of assessing IL-22, IL-23 and IL-22BP in real-world studies. Methods: A search was undertaken in MEDLINE and Embase to identify English-language manuscripts (2018-2021) and conference abstracts (2019-2021) of real-world studies in adult IBD, measuring IL-22, IL-23, or IL-22BP. One reviewer screened titles/abstracts for eligibility using a standardized form. A second reviewer independently screened a random sample of publications and disagreements were resolved by a third reviewer. Results: Titles and abstracts of 369 studies were screened. Forty-two studies met the eligibility criteria and were included for full-text screening. Seventeen studies were then excluded because they lacked key information such as the study design or the clinical application. A total of 25 studies were included. Of those, three were conference abstracts. Nine (36%), eight (32%), and eight (32%) studies included patients with CD only, UC only, and both CD and UC with/without their comparison groups, respectively. Eleven studies (44%) were conducted in Europe, 10 (40%) in Asia, two (8%) in North America, and one (4%) each in Africa and the Middle East. Twelve (48.0%) studies reported on IL-23, 11 (44.0%) on IL-22 and one (4.0%) on IL-22BP. Most publications reported on more than one IL with multiple applications. Eight (28%) studies examined diagnostic applications, 11 (38%) prediction of severity, and 10 (34%) prediction of treatment response. Multiple sampling sources were used, including tissue (38%), serum (34%), cell (16%), blood(9%), and plasma (3%). IL-23 levels were consistently correlated with IBD severity when comparing IBD with healthy controls, but the data was less consistent for IL-23 as a diagnostic test or predictor of treatment response. The reported correlations for IL-22 and IL-22BP varied across studies. This was potentially due to heterogeneous study methodologies. Conclusion: This literature review shows that IL-22, IL-22BP and IL-23 have been studied in the real world for diagnosis, prediction of disease severity, and treatment response in IBD; however, there was heterogeneity in methodologies, ethnic composition, and sample types across studies. The correlation of IL-22 level with the studied outcomes was qualitatively inconsistent across studies and applications, whereas IL-23 was found to be consistently associated with IBD severity.